Penerapan Metode Left Corner Parsing dan Analisis Kontekstual Pada Natural Language Processing - Deny Jollyta; Muhammad Zarlis; Gusrianty Gusrianty; Yulvia Nora Marlim (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
Natural language translation is very helpful in understanding each word or sentence based on the intended meaning. Variety of languages that are not easy to understand, cause miscommunication. Natural Language Processing (NLP) is the choice to translate human language with computer naturally. As one method of parsing, the left corner parsing describes languages ranging from the largest to the smallest constituent, namely the word. The decomposition is followed by representing the meaning or known as contextual interpretation. This study aims to describe the language using the left corner parsing which is equipped with analysis to determine the purpose of sentence using. The test results showed that the Left Corner Parsing method succeeded in deciphering sentences in accordance with the initial language pattern specified and provided the true contextual analysis and easily understood translation results.